2015
DOI: 10.1270/jsbbs.65.265
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of feral genetically modified herbicide-tolerant <i>Brassica napus</i> populations around unloading Japanese ports

Abstract: Genetically modified, herbicide-tolerant (GMHT) Brassica napus plants originating from seed spill have recently been found along roadsides leading from Japanese ports that unload oilseed rape. Such introductions have potential biodiversity effects (as defined by the Cartagena Protocol): these include replacement of native elements in the biota through competitive suppression or hybridization. We conducted surveys in the period 2006–2011 to assess such threats. We examined shifts in the population distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 51 publications
(34 reference statements)
3
32
0
Order By: Relevance
“…Subsequently, transgenes must be transmitted through successive backcross generations or selfing, so that they become stabilised into the genome of the recipient (de Jong and Rong, ; Garnier et al., ). Because of these barriers (Luijten et al., ), reported incidences of hybrids and backcrosses with B. rapa were therefore found to be low in fields (Jørgensen et al., ; Norris et al., ; Warwick et al., ; Elling et al., ), or at ports, along roadsides, and riverbanks (Saji et al., ; Aono et al., , ; Yoshimura et al., ; Elling et al., ; Katsuta et al., ; Luijten et al., ).…”
Section: Risk Assessment Of the Three‐event Stack Oilseed Rape Ms8 × mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, transgenes must be transmitted through successive backcross generations or selfing, so that they become stabilised into the genome of the recipient (de Jong and Rong, ; Garnier et al., ). Because of these barriers (Luijten et al., ), reported incidences of hybrids and backcrosses with B. rapa were therefore found to be low in fields (Jørgensen et al., ; Norris et al., ; Warwick et al., ; Elling et al., ), or at ports, along roadsides, and riverbanks (Saji et al., ; Aono et al., , ; Yoshimura et al., ; Elling et al., ; Katsuta et al., ; Luijten et al., ).…”
Section: Risk Assessment Of the Three‐event Stack Oilseed Rape Ms8 × mentioning
confidence: 99%
“…Survival of oilseed rape outside cultivation areas is possible. Demographic studies and surveys have shown the ability of oilseed rape (B. napus) to establish self-perpetuating populations outside agricultural areas, mainly in seminatural and ruderal habitats in different countries (reviewed by Devos et al, 2012;Bauer-Panskus et al, 2013;COGEM, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Busi and Powles, 2016;Nishizawa et al, 2016). oilseed rape is generally regarded as an opportunistic species, which can take advantage of disturbed sites (e.g.…”
Section: Potential Unintended Effects On Plant Fitness Due To the Genmentioning
confidence: 99%
“…By multiplying the cultivation ratio (97.5%) and the volume imported (2.4 million tons) together, approximately 2.2 million tons of GM B. napus are apparently being imported to Japan each year. GM B. napus derived from spilled seeds have been found over the years along roads around the oilseed import ports in Japan (Katsuta et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…EFSA considers that the dataset gathered by Pascher et al (2016) confirms and complements the current knowledge on the biology and population demographics of feral oilseed rape. Demographic studies and surveys performed in the EU or abroad have shown the ability of oilseed rape to establish self-perpetuating populations outside agricultural areas, mainly in semi-natural and ruderal habitats in different countries (reviewed by Devos et al, 2012;Bauer-Panskus et al, 2013;COGEM, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Busi and Powles, 2016;Nishizawa et al, 2016).…”
Section: Novelty Of Gathered Evidencementioning
confidence: 99%